Parenting and Temperament Influence on School Success in 9–13 Year Olds - Checa, Purificación; Abundis-Gutierrez, Alicia (Frontiers in Psychology, 2017)
Children spend a lot of time with their parents who are the first agents that edu-cate them. The parenting style implemented in the family influences other contexts out-side home such as the school. There is evidence that a positive parenting style has an influence on school success. However, there are other variables related to school success, for example, temperament. The influence of parenting decreases with age as children develop abilities to self-regulate without parents’ external control. The aim the present study was to evaluate the contribution of parenting style and temperament in 9-13 years old children on both academic performance and school adjustment skills. Our hypothesis was that not only parenting style is crucial to academic performance and school adjustment, but also temperament plays an important role in them. We used a Parenting Guide line questionnaire to evaluate parenting style, Early Adolescence Temperament Questionnaire-R to evaluate temperament, Health Resources Inventory to assess children’s school adjustment, and academic grades, as measured of academic performance. We were interested in testing whether or not the effect of parenting style on academic performance and school adjustment was mediated by temperament. We found that emo-tional and behavioral regulation mediates the relation between parenting and academic performance. These findings inform of the relevance of child’s temperament on school success. Implications for education are discussed emphasizing the importance of under-standing student's temperament to promote school adjustment and good academic per-formance.